2017
DOI: 10.3390/toxins9090256
|View full text |Cite
|
Sign up to set email alerts
|

Spectral EMG Changes in Cervical Dystonia Patients and the Influence of Botulinum Toxin Treatment

Abstract: Botulinum toxin (BoNT) injections in the dystonic muscles is the preferred treatment for Cervical Dystonia (CD), but the proper identification of the dystonic muscles remains a challenge. Previous studies showed decreased 8–14 Hz autospectral power in the electromyography (EMG) of splenius muscles in CD patients. Cumulative distribution functions (CDF’s) of dystonic muscles showed increased CDF10 values, representing increased autospectral powers between 3 and 10 Hz, relative to power between 3 and 32 Hz. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…Regarding the proportion of patients who had previously been treated with BoNT-A, it was high, and considering an average of 7.3 months between the last treatment and enrollment, we could suggest that subjects continue to receive benefit from repeated and previous treatments. Although the proper identification of the dystonic muscles remains a challenge 11 , the principal injected muscles in this study remain similar to those most frequently described in the previous studies 12 .…”
Section: Discussionsupporting
confidence: 63%
“…Regarding the proportion of patients who had previously been treated with BoNT-A, it was high, and considering an average of 7.3 months between the last treatment and enrollment, we could suggest that subjects continue to receive benefit from repeated and previous treatments. Although the proper identification of the dystonic muscles remains a challenge 11 , the principal injected muscles in this study remain similar to those most frequently described in the previous studies 12 .…”
Section: Discussionsupporting
confidence: 63%
“…2) [9] compared to other studies using only inspection or goniometer for ROM evaluation [16][17][18][19]. Using surface EMG we could not show significant changes which maybe related to the known vulnerability to artifacts of EMG [20] and the measurement of standardized muscles (i. e, sternocleidomastoid muscle, trapezius muscle) rather than of individually clinically involved muscles.…”
Section: Resultsmentioning
confidence: 64%
“…Quantitative signatures of dystonic muscles were most clear and most significant in the cumulative density function of EMG between 3-10 Hz, which was defined as the ratio of power in the lower (3-10 Hz) band to the 3-30 Hz band (Bruijn et al, 2017a). Previous studies have shown increased CDF10 values in CD patients, representing higher signal power between 3 and 10 Hz, relative to power between 3 and 30 Hz (Nijmeijer et al, 2017) (Figure 1). Furthermore, with a cut-off value of CDF10 = 0.222, in an isometric contraction task dystonic muscles in CD patients can be identified from non-dystonic muscles in healthy controls (Nijmeijer et al, 2017).…”
Section: Electrophysiological Signatures Of CDmentioning
confidence: 87%
“…Although no uniform electrophysiological feature was concluded as the general feature of the dystonic movement, there has been a hypothesis that a downward shift in the power of EMG signal exists in dystonic compared to non-dystonic muscles (Tijssen et al, 2000b;Nijmeijer et al, 2014Nijmeijer et al, , 2017Bruijn et al, 2017a). In line with the hypothesis, studies have shown that power of EMG between 3-10 Hz in CD patients is higher than healthy individuals during isometric contractions (Nijmeijer et al, 2014).…”
Section: Electrophysiological Signatures Of CDmentioning
confidence: 99%